2010
DOI: 10.1071/hc10225
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner perceptions of clinical medication reviews undertaken by community pharmacists

Abstract: INTRODUCTION: Delivery of current health care services focuses on interdisciplinary teams and greater involvement of health care providers such as nurses and pharmacists. This requires a change in role perception and acceptance, usually with some resistance to changes. There are few studies investigating the perceptions of general practitioners (GPs) towards community pharmacists increasing their participation in roles such as clinical medication reviews. There is an expectation that these roles may be perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…Other studies which have explored different issues related to CP and GP collaboration have found similar results, indicating that this would improve the quality of the prescription (Bryant et al, 2010a;Montgomery et al, 2007;Teinilä, Kaunisvesi, & Airaksinen, 2011) (Dieleman et al, 2004;Howard et al, 2003) and would increase patient trust (Montgomery et al, 2007).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Other studies which have explored different issues related to CP and GP collaboration have found similar results, indicating that this would improve the quality of the prescription (Bryant et al, 2010a;Montgomery et al, 2007;Teinilä, Kaunisvesi, & Airaksinen, 2011) (Dieleman et al, 2004;Howard et al, 2003) and would increase patient trust (Montgomery et al, 2007).…”
Section: Discussionmentioning
confidence: 51%
“…Factors which influence collaboration are diverse and range from time and funding to those which depend on approach, such as trust and respect (Bradley, Ashcroft, & Noyce, 2012;Hughes & McCann, 2003;Rubio-Valera et al, 2012). One of the most relevant factors in promoting or initiating the GP-CP relationship is the perception that these professionals have regarding the usefulness of the collaboration (Bryant et al, 2010a).…”
Section: Introductionmentioning
confidence: 98%
“…One study combined qualitative interviews and a survey . Studies were conducted in 13 countries, most commonly Australia (n=3), New Zealand (n=3), and the Netherlands (n=3) …”
Section: Resultsmentioning
confidence: 99%
“…Monitoring‐related problems accounted for more than two DRPs per patient, but were mostly assigned a low priority and not followed by a recommendation for drug change. Monitoring‐related problems and some other DRPs identified by expert reviewers might be perceived by community pharmacists and GPs as too theoretical or ‘textbook advice’ . This may partly explain why community pharmacists identified a lower number but relatively more clinically relevant DRPs.…”
Section: Discussionmentioning
confidence: 99%